Transnationalism and mental spaces: a perspective on the global mind - Emilia URSACHI (HASMAȚUCHI) (Eon, 2024)
The concept of transnationalism has become increasingly relevant in today's globalized world, as people and ideas move across borders more freely than ever before, developing a unique mental space that is influenced by their diverse experiences and interactions with different cultures. Understanding transnationalism and mental spaces is crucial to comprehending the complexities of identities, as it sheds light on how individuals negotiate their multiple cultural identities, in a world that is constantly changing and interconnected.